Alterations of Prefrontal-Posterior Information Processing Patterns in Autism Spectrum Disorders - Zhao, Hai-Chen; Lv, Rui; Zhang, Guang-Yu; He, Le-Min; Cai, Xiao-Tao; Sun, Qiang; Yan, Chun-Yan; Bao, Xiang-Yuan; Lv, Xin-Yue; Fu, Bin (Frontiers in Neuroscience, 2022)
Autism spectrum disorder (ASD) is a heterogeneous disorder characterized by different levels of repetitive and stereotypic behavior as well as cognitive deficits. In this current study, we explored the changes in cerebral neural activities in ASD. The purpose of this study is to provide some implications for the clinical diagnosis and treatment of ASD. We investigated the atypical connectivity and information flow between the prefrontal cortex and posterior brain regions of ASD utilizing the entropy connectivity (a kind of directional connectivity) method and predictive coding theory. Eighty-nine patients with ASD and 94 age-matched typical developing (TD) teenagers participated in this study. Two-sample t-tests revealed weakened bidirectional entropy connectivity between the prefrontal cortex and posterior brain regions, which indicated decreased top-down control and bottom-up information input in patients with ASD. In addition, we also found a blocked frontal-posterior information flow circuit based on predictive coding theory. We explored the potential influence of this blocked circuit. We considered that the disorder of top-down control and bottom-up information input might lead to less prior knowledge being used and updated, and the posterior cortices occupy more neural resources as a consequence of the blocked frontal-posterior information flow circuit. Our proposals highlighted that a combination of abnormal top-down and bottom-up information processing accelerates the deoptimization of brain networks and potentially affects cognitive activities in patients with ASD.